Super Resolution Microscopy of SUMO Proteins in Neurons - Colnaghi, Luca; Russo, Luca; Natale, Carmina; Restelli, Elena; Cagnotto, Alfredo; Salmona, Mario; Chiesa, Roberto; Fioriti, Luana (Frontiers in Cellular Neuroscience, 2019)
The ubiquitously expressed SUMO proteins regulate a plethora of cellular pathways and processes. While they have a predominantly nuclear localization, extranuclear roles of SUMO isoforms at the synapse have also been described, making SUMOylation one of the major post-translational regulators of nerve functions. These findings have however recently been challenged, at least for SUMO1, by the analysis of transgenic SUMO1 knock-in mice, where the authors failed to detect the protein at the synapse. In the ongoing dispute, the subcellular distribution in neurons of SUMO2/3 and of the E2 SUMO ligase Ubc9 has not been examined. To investigate whether SUMO proteins do or do not localize at the synapse, we studied their localization in hippocampal primary neurons by super resolution microscopy. We found that SUMO1, SUMO2/3 and Ubc9 are primarily nuclear proteins, which also colocalize partially with pre- and post-synaptic markers such as synaptophysin and PSD95.